Zwitterionic coating assisted by dopamine with metal-phenolic networks loaded on titanium with improved biocompatibility and antibacterial property for artificial heart - Meng, Lingwei; Huang, Chuangxin; Liu, Xin; Qu, Hongyi; Wang, Qiuliang (Frontiers in Bioengineering and Biotechnology, 2023)
Titanium (Ti) and its alloys are the predominant materials for artificial hearts. To prevent infection and thrombus, patients with implanted artificial hearts need to take antibiotics and anti-thrombotic drugs for a long time, which can easily lead to many complications. Therefore, the development of antibacterial and antifouling coatings on the titanium surface is extremely important for artificial hearts. Polydopamine (PDA) and poly-(sulfobetaine methacrylate) (PSBMA) were co-deposited to form a coating on Ti initiated by Cu2+ in this paper. The fabrication mechanism of the coating was investigated by UV-Vis spectroscopy, coating thickness and XPS measurements. Optical images, SEM, XPS, AFM, water contact angle, and film thickness test results demonstrated that the coating was formed on Ti successfully. In addition, the antibacterial properties of the coating were tested using Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), while the biocompatibility of the coating was evaluated by the in vitro cytotoxicity tests on human umbilical vein endothelial cells (HUVECs) and red blood cells (RBCs), and the antiplatelet adhesion test. The good biocompatibility and antibacterial effectiveness of the coating indicate that the coating has great potential for improving the antibacterial and antiplatelet adhesion properties of Ti.